Examination of paraffin-embedded testes of domestic cats and dogs by light and scanning electron microscopy - Banu Kandil; Beste Demirci; Alev Gürol Bayraktaroğlu; Emre Demirci (Elsevier BV, 2025)
This study was designed to determine the appropriate section thickness for SEM analysis of paraffin-embedded testes. This study used paraffin-embedded testes from 6 adult cats and 6 adult dogs. Tissue blocks were cut into 10, 20, and 40 µm thick sections and analyzed by SEM. In addition, seminiferous tubule and lumen diameter and germinative epithelium height were measured in 10 and 20 µm thick paraffin sections. Measurements from 10 and 20 µm thick paraffin sections showed that the height of the germinative epithelium and the diameter of the lumen and tubules were similar between cats and dogs (p > 0.05). In cats and dogs, tubule diameter and germinative epithelium height were higher in the 10 µm thick paraffin sections compared to the 20 µm thick paraffin sections. However, in both species, the lumen diameter was greater in the 20 µm thick paraffin sections than in the 10 µm thick paraffin sections (p < 0.05). Unlike 40 µm thick paraffin sections, 10 and 20 µm thick paraffin sections allowed the structural features of the testes to be examined. Additionally, 10 µm thick paraffin sections were ideal for histometric measurements, while 20 µm thick paraffin sections were suitable for detailed examination of late spermatids. The present study showed that testes may be examined in detail by SEM from 10 and 20 µm thick paraffin sections. In addition, this study may contribute to the design of new studies to reveal the missing three-dimensional structures of paraffin-embedded testicular tissues stored in tissue archives by analyzing them by SEM.
Keywords: Testis; Tissue archives.; Paraffin section; Scanning electron microscopy; Histology depositories